The effect of teaching provided through interactive infographics on the social skills of children with intellectual disabilities - Gulmus Yelmen, Merve; Turel, Yalin Kilic (Routledge, 2025)
This study aims to explore the effects of interactive infographic-based instruction on the social skills of preschool children (aged 60–72 months) with mild intellectual disabilities. The interactive infographic, developed specifically for the research, was employed using the direct teaching method to facilitate the learning of social skills typically acquired by children through natural observation. The research utilised an ABA design, a single-subject experimental model, involving three preschool children with mild intellectual disabilities (one female, two males) within the specified age range, as well as their teachers. The study spanned an initial teaching phase, followed by post-implementation assessments at two and three weeks to evaluate skill retention. Findings indicated a significant improvement in the social skills of the participants following the interactive infographic-based instruction delivered through the direct teaching approach. These improvements were observed to be largely maintained during the follow-up assessments, suggesting the effectiveness of the intervention in fostering long-term skill acquisition. The study concludes that interactive infographic-based instruction can effectively enhance the social skills of young children with mild intellectual disabilities. Teacher interviews further supported these findings, providing positive social validity data and affirming the practical applicability and benefits of the instructional approach used. © 2025 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: direct teaching method; intellectual disability; Interactive infographic; social skills teaching